Post-cinema Cinema in the Post-art Era - Chateau, Dominique; Moure, José (The Key Debates: Mutations and Appropriations in European Film Studies, 2020)
This volume explores new ways of considering, experiencing and making films in a time of technological transition. It brings together an international group of scholars and artists from a variety of countries, who speak different languages and come from different cultural and disciplinary backgrounds.